Acute Respiratory Barrier Disruption by Ozone Exposure in Mice - Sokolowska, Milena; Quesniaux, Valerie F. J.; Akdis, Cezmi A.; Chung, Kian Fan; Ryffel, Bernhard; Togbe, Dieudonnée (Frontiers in Immunology, 2019)
Ozone exposure causes irritation, airway hyperreactivity (AHR) and inflammation of the airways in man and mice. This review focuses on the acute disruption of the respiratory barrier in mice. A single high dose ozone exposure (1 ppm for 1h) causes first a break of the respiratory barrier within 2h with leak of serum proteins in the broncho-alveolar space, disruption of epithelial tight junctions and cell death, which is followed at 6h by ROS activation, AHR, myeloid cell recruitment and remodeling. High ROS levels activate the phosphatase PGAM5 activating AIFM1 (mitochondrial apoptosis inducing factor 1) leads to a novel form of cell death known as oxeiptosis. In absence of PGAM5 ozone-induced lung inflammation and injury is increased. While acute exposure is reversible, chronic exposure leads to loss of alveolar septae with emphysema and lung fibrosis. Recent data on the mechanisms of ozone induced injury on the different cell types and pathways with a focus on the role of the IL-1 family cytokines and the related IL-33.